The Evolution of Exudativory in Primates 2010
DOI: 10.1007/978-1-4419-6661-2_13
|View full text |Cite
|
Sign up to set email alerts
|

Tongue Morphology in Infant and Adult Bushbabies (Otolemur spp.)

Abstract: Lingual fungiform papillae are the only structures on the anterior two-thirds of the tongue that contain taste receptor cells and are the first gustatory structures to encounter food items. In humans, density of fungiform papillae is associated with taste sensitivity and food selection. Nonhuman primates also use the sense of taste to detect the nutritional contents of potential food items. The present study examines the ontogeny, distribution, and density of fungiform papillae in two species of greater bushba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Few studies have explored variations in TP density or count in nonhuman primates because TPs are difficult to view except by electron microscopy (Docherty et al,2010). We found that TP count within a single FP did not differ significantly between males and females.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Few studies have explored variations in TP density or count in nonhuman primates because TPs are difficult to view except by electron microscopy (Docherty et al,2010). We found that TP count within a single FP did not differ significantly between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…However, these negative findings may be a result of histological section thickness (>20 μm) or too few serial sections (<15). Although TBs are rarely missed because they range between 10 and 20 μm, it is possible to miss one in intervals between stained sections (Docherty et al,2010). Because males in the study had smaller FP, but equal number of TPs per FP, males were documented to have significantly higher TP densities than females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations